Transferencia de conocimiento pedagógico en hospitales universitarios (2020)
Introduction: Knowledge transfer as a result of pedagogical research aims at improving quality processes in university hospitals and at strengthening the human conception of professional work. Objective: To identify the theoretical foundations of knowledge transfer as a result of pedagogical research in hospital settings. Methods: An exploratory study was carried out following a qualitative approach and conducting 22 semistructured interviews with different health professionals in their real settings. This information was systematized through coding and comparison processes, typical of grounded theory, through the construction of diagrams for the compilation of concepts, properties and dimensions. Results: Through information analysis, five categories were established: knowledge to transfer, key actors for transfer, transfer methodology, hospital setting and universityhospital relationship; together with eight subcategories related to transfer of pedagogical knowledge. From the analysis of this information, theoretical foundations were proposed, based on a student-centered and patient care–oriented adaptive process. Conclusions: Theoretical foundations for the transfer of pedagogical knowledge in hospital contexts were established, through the identification of an adaptive system, which contains key elements for improving the effectiveness in the relationship with the patients and their care.